KREATIVITAS “COOKING CAKE DAN CV” SEBAGAI SKILL DEVELOPMENT ANAK SEKOLAH KEJURUAN DI KOTA PEMATANGSIANTAR, SUMATERA UTARA - Novriani Tambunan; Malida Putri (Universitas Trisakti, 2022)
This service activity is motivated by the need for self-development of vocational school children after graduating from school. On this basis, it is very important to launch a competency improvement program for prospective graduates through several training activities and courses. The purpose of this activity is to facilitate group members to develop and achieve social change and goals as well as the desired benefits, namely by building skills and good cooperation between members through cooking cake training activities in self-development for these vocational school children. One of the activities that can be carried out by setting a priority program is holding cooking classes in the hope of increasing their skills and deepening their knowledge of economical and hygienic food and developing new soft skills (a program based on the common hobbies of group members). The method of implementing this activity is based on the theory in the Social Welfare Study Program, namely using the Mezzo level with intervention or a Group Work method or group approach (Based on the theory of Zastrow, 2004:50-54). The stages include the intake stage (building relationships), the assessment and intervention planning stage, the member selection stage, the group development stage, and finally the evaluation and termination stage (the stage of severing relations with the client/target group). The target of this activity is five Vocational High School (SMK) children who are doing practicum at the Social Service Office, Jl. Dahlia, Pematangsiantar City.KREATIVITAS “COOKING CAKE DAN CV” SEBAGAI SKILL DEVELOPMENT ANAK SEKOLAH KEJURUAN DI KOTA PEMATANGSIANTAR, SUMATERA UTARA